ICT, High-Tech Exports, and Institutions as Drivers of Bank Expansion Growth in a Dual Banking System - Sulaeman Sulaeman; Arizal Tom Liwafa; Bayu Arie Fianto (Journal of Islamic Monetary Economics and Finance, 2026)
This study examines how information and communication technology (ICT) adoption, high-tech exports (HTE), and institutional quality (IQ) influence bank-level expansion growth (BEG) in 218 Islamic and conventional banks operating in 12 countries from 2010 to 2023. Using bank-level panel data analysis, the results reveal that ICT adoption is the most powerful driver of bank expansion growth, reinforcing digital transformation as a universal catalyst for efficiency, competitiveness, and outreach. While HTE alone has a limited and statistically insignificant effect, its interaction with ICT generates a significant synergistic impact, indicating that national innovation capacity amplifies the growth benefits of digitalization. Institutional quality exhibits a positive but indirect role, functioning primarily as an enabling condition that supports bank expansion—particularly for Islamic banks—through stronger governance and regulatory credibility. Comparative findings show that Islamic banks rely more on institutional integrity and technological complementarity, whereas conventional banks depend more on operational efficiency and digital maturity. Robustness checks using dynamic panel estimators confirm the consistency of these relationships. Policy implications highlight the importance of strengthening digital infrastructure, promoting high-tech innovation, and improving institutional governance to foster sustainable and inclusive bank expansion within a dual banking framework.